2021
DOI: 10.3389/fgene.2020.574167
|View full text |Cite
|
Sign up to set email alerts
|

Dysregulated H3K27 Acetylation Is Implicated in Fatty Liver Hemorrhagic Syndrome in Chickens

Abstract: Epigenetic regulation of gene expression has been reported in the pathogenesis of metabolic disorders such as diabetes and liver steatosis in humans. However, the molecular mechanisms of fatty liver hemorrhagic syndrome (FLHS) in chickens have been rarely studied. H3K27ac chromatin immunoprecipitation coupled with high-throughput sequencing and high-throughput RNA sequencing was performed to compare genome-wide H3K27ac profiles and transcriptomes of liver tissue between healthy and FLHS chickens. In total, 1,3… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
11
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 13 publications
(14 citation statements)
references
References 83 publications
2
11
0
Order By: Relevance
“…Previous study reported that great changes genome-wide H3K27ac profiles changed a lot in the liver of FLHS chicks ( Zhu et al, 2020 ). Consistent with the results in the present study, hepatic total H3K27ac and H3K4me2 levels were different among 3 embryonic days.…”
Section: Discussionmentioning
confidence: 98%
“…Previous study reported that great changes genome-wide H3K27ac profiles changed a lot in the liver of FLHS chicks ( Zhu et al, 2020 ). Consistent with the results in the present study, hepatic total H3K27ac and H3K4me2 levels were different among 3 embryonic days.…”
Section: Discussionmentioning
confidence: 98%
“…Similar to its function in mammals [ 115 ], PPARα exerts function in regulating the related pathways with lipid-lowering effect in chickens [ 16 , 123 ]. The activation of PPARα is suppressed in FLHS chickens [ 124 , 125 ]. Chen et al [ 124 ] cloned and synthesized PPARα protein for producing chicken polyclonal antibodies and showed that the expression of PPARα was decreased in FLHS chickens.…”
Section: Molecular Mechanism Of Osteocalcin In Flhs Chickensmentioning
confidence: 99%
“…Chen et al [ 124 ] cloned and synthesized PPARα protein for producing chicken polyclonal antibodies and showed that the expression of PPARα was decreased in FLHS chickens. Zhu et al [ 125 ] reported that high energy and low protein diet (HELP), one of the natural causes of chicken FLHS, dysregulated the PPARα signaling pathway, causing excessive accumulation of fat in the liver tissue with the potential to develop FLHS in chickens.…”
Section: Molecular Mechanism Of Osteocalcin In Flhs Chickensmentioning
confidence: 99%
“…A widespread H3K27ac dysregulation in the liver of FLHS-affected chickens was observed, and FLHS-associated variations in H3K27ac marks were associated with known FLHS risk genes involved in lipid and energy metabolism ( pck1 , apoa1 , angptl4 , and fabp1 ) and immune function ( fgf7 , pdgfra , and kit ). Furthermore, the PPAR signaling pathway was most significantly enriched in FLHS [ 162 ]. Interestingly, this pathway was also highlighted in an integrated analysis of the methylome and transcriptome in FLHS chicken.…”
Section: Estrogen Associated Liver Diseases In Oviparous Vertebratesmentioning
confidence: 99%